Tribuana Manggala Bakti: Menjaga Lingkungan Alam Menoreh dalam Perspektif Fritjof Capra - Suharno Suharno; Sartini Sartini (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2022)
There are many Buddhist religious rituals in Indonesia. One of them is Tribuana Manggala Bakti which contains universal values in nature conservation. The purpose of this study is to describe the dynamics of the Menoreh community in terms of managing the natural environment, to describe Tribuana Manggala Bakti as Buddhist spirituality, and to analyze the role of Tribuana Manggala Bakti spirituality with universal values in Menoreh environmental management. This research is a qualitative research with library research. This study uses the theory of using Capra's holistic spiritual theory in understanding the function and purpose of Tribuana Manggala Bakti. Menoreh's natural resource management started from an ideational culture to a sensate culture. Sensate culture is seen when people begin to exploit natural resources. Tribuana Manggala Bakti originated from the concern of Buddhists towards the Menoreh nature. Tribuana Manggala Bakti is a series of Vesak events in the form of taking Vesak holy water followed by tree planting, and releasing fish and birds. The release of animals and the planting of trees as a tangible form of awareness of the importance of nature underlies the behavior of an environmentally friendly lifestyle, protecting and caring for the environment. As said by Fritjof Capra as one of the real solutions to the environmental crisis. In Ecoliteracy Capra, realizing the importance of nature has an impact on environmentally friendly lifestyle behavior, protecting and caring for the environment.